The impact of theatre on empathy and self-esteem: a meta-analysis. Issue 3 (2nd July 2020) - Lewandowska, Kamila; Węziak-Białowolska, Dorota
ABSTRACT: This study presents the results of meta-analyses evaluating the effects of active theater on empathy and self-esteem. The effect size of the impact of theater-making on empathy showed that theater has a positive, although moderate influence on empathic abilities. The meta-analysis concerning self-esteem did not confirm the impact of active theater on the outcome in question, but this result should be treated with caution due to heterogeneity. The meta-regression, in which type of participants, control group activity, duration and frequency of interventions, type of measurement scale, group allocation method, setting, and publication year were controlled for, corroborated these results.